(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Water is a resource with the capacity to generate power in many forms whether be it access to drinking water or use as hydropower or steam power to produce electricity. Renewable recourses open issues where environmental protection meets different requirements: to protect the quality and national potential of water, but to develop the use of emission-free hydropower; to strengthen constitutional and legal guaranties to access to water but to provide adequate type of rights to use hydropower. The right to use water for hydropower must be weighed with its impact on the quality and quantity of water courses. In comparative law we may find different approaches that should guarantee the right to water. The concept that the right to water might be protected only if water is recognized as a legal person (exercised in recent cases the Amazon River, Ganges and Yamuna rivers, Whanganui river) will be challenged with EU approach where measurement on different interests of environmental protection is the base for water protection. The article outline elements that provide minimum guarantees for including the both rights in decision-making process singled out in practice of jurisprudence of the Court of Justice of the European Union. The article points out the most important case under the Serbian Administrative Court on small hydropower licensing in 2018. The aim of the article is to examine if the conclusions from EU may be find in Serbian law and to suggest legal changes that could lead to full transposition of environmental acquis.